Health Costs and Benefits of DDT Use in Malaria Control and Prevention - Blankespoor, Brian; Dasgupta, Susmita; Lagnaoui, Abdelaziz; Roy, Subhendu (World Bank, Washington, DC, 2013)
The Millennium Development Goal of achieving near-zero malaria deaths by 2015 has led to a re-examination of wider use of DDT (dichloro-diphenyl-trichloro-ethane) in indoor residual spraying as a prevention tool in many countries. However, the use of DDT raises concerns of potential harm to the environment and human health, mainly because of the persistent and bio-accumulative nature of DDT and its potential to magnify through the food chain. This paper quantifies the adverse effects of DDT on human health based on treatment costs and indirect costs caused by illnesses and death in countries that use or are expected to re-introduce DDT in their disease vector control programs. At the global level where the total population exposed to DDT is estimated around 1.25 billion, the findings indicate that while the use of DDT can lead to a significant reduction in the estimated $69 billion in 2010 U.S. dollars economic loss caused by malaria, it can also add more than $28 billion a year in costs from the resulting adverse health effects. At the country level, the results suggest that Sub-Saharan African countries with high malaria incidence rates are likely to see relatively larger net benefits from the use of DDT in malaria control. The net health benefits of reintroducing DDT in malaria control programs could be better understood by weighing the costs and benefits of DDT use based on a country's circumstances.